Neutral pH and low-glucose degradation product dialysis fluids induce major early alterations of the peritoneal membrane in children on peritoneal dialysis - Schäfer, Betti; Bartosova, Maria; Lasitschka, Felix; Romero, Philipp; Schaefer, Franz; Ujszaszi, Akos; Schmitt, Claus P. (Kidney international, 2018)
The effect of peritoneal dialysates with low-glucose degradation products on peritoneal membrane morphology is largely unknown, with functional relevancy predominantly derived from experimental studies. To investigate this, we performed automated quantitative histomorphometry and molecular analyses on 256 standardized peritoneal and 172 omental specimens from 56 children with normal renal function, 90 children with end-stage kidney disease at time of catheter insertion, and 82 children undergoing peritoneal dialysis using dialysates with low-glucose degradation products. Follow-up biopsies were obtained from 24 children after a median peritoneal dialysis of 13 months. Prior to dialysis, mild parietal peritoneal inflammation, epithelial-mesenchymal transition and vasculopathy were present. After up to six and 12 months of peritoneal dialysis, blood microvessel density was 110 and 93% higher, endothelial surface area per peritoneal volume 137 and 95% greater, and submesothelial thickness 23 and 58% greater, respectively. Subsequent peritoneal changes were less pronounced. Mesothelial cell coverage was lower and vasculopathy advanced, whereas lymphatic vessel density was unchanged. Morphological changes were accompanied by early fibroblast activation, leukocyte and macrophage infiltration, diffuse podoplanin presence, epithelial mesenchymal transdifferentiation, and by increased proangiogenic and profibrotic cytokine abundance. These transformative changes were confirmed by intraindividual comparisons. Peritoneal microvascular density correlated with peritoneal small-molecular transport function by uni- and multivariate analysis. Thus, in children on peritoneal dialysis neutral pH dialysates containing low-glucose degradation products induce early peritoneal inflammation, fibroblast activation, epithelial-mesenchymal transition and marked angiogenesis, which determines the PD membrane transport function.
Gesehen am 23.05.2019